Enrichment of Organic Manure with Plant Growth Promoting Rhizobacteria Improved the Root and Shoot Growth of Okra (Abelmoschus esculentus L. Moench.) - Magana, Richard Elisha; Melati, Maya; Purnamawati, Heni; Pratiwi, Etty (Journal of Tropical Crop Science, 2020)
A well-structured root system is essential to ensure optimal plant growth and yield. Two experiments were conducted to determine the effects of plant growth promoting rhizobacteria (PGPR) on the root system of okra plant. These experiments were arranged with a completely randomized design. The first experiment was conducted in the growth chamber with 8 different bacterial isolates consisting of Methylobacterium sp., Bacillus sp., Bacillus methylotrophicus, Flavobacterium tirrenicum, Providencia stuartii, Azotobacter vinelandii, Methylocystis parvus and PGPR consortium. The second experiment was conducted in the greenhouse and examined the effects of four poultry manure rates, i.e. 0, 6, 12 and 18 ton ha-1, or equivalent to 0, 75, 150 and 225% of recommended rates and how these are altered with the presence or absence of PGPR. The results of the experiments showed that, PGPR significantly improved root architecture; the number and length of lateral roots was increased by 242.86% and 777.79% respectively, as well as the dry weight of the roots and shoots of okra plant by 236.36% and 333.33%, respectively. Moreover applying 150% (12 t.ha-1) of the recommended rate of poultry manure enriched with PGPR was found to be most effective in terms of improving the growth and root attributes of okra plants.